Theoretical Study of the Photons Production Kinetic In Hot Quark-Gluon Plasma Matter - J.M. Al-agealy, Hadi; Qays Ghadhban, Rawnaq; A. Hassooni, Mohsin (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
In this paper, we study flow of photons rate production in a quark-gluon QG plasma. General theory of this study is based on the field theory for hard interaction. The kinetic of photons production from hard interaction in charm with anti-top to production photons with gluon due to plasma phase at high temperatures (150, 200,250,300 and 350 MeV) .It has been investigated and studied using the postulate of quantum chromodynamic theory QCD .The photons production rate of hard photons with( GeV) are insensitive to strength coupling and depend mainly on the temperature of system T . Despite the different critical temperature (150 and 190MeV) comes, we ï¬nd that same order of flow rate photons magnitude in both cases. In both cases, the flow rate of photons production in the QG plasmais increased with increased temperature of system and photons energy and decreases with increases the strength coupling strength.